Preparation Of Biochar From Palm Oil Mill Effluent (Pome) Sludge By Microwave Pyrolysis - Au, Jia Yu (Universiti Sains Malaysia, 2022)
The characteristics and adsorption application of biochar produced from Palm Oil Mill Effluent (POME) Sludge by microwave pyrolysis has been presented in this report. This study was carried out to study the production of biochar from POME sludge by microwave pyrolysis, the effect of microwave power, and radiation time on the biochar yield and its characteristics. Besides, this study was also aimed to evaluate the feasibility of using biochar to reduce turbidity of POME by removing the colour contaminants in POME. Microwave pyrolysis by using Nitrogen (N2) gas as purge gas was used to produce biochar. The optimum pyrolysis setup condition of the biochar for best turbidity reduction of POME performance is at a microwave power of 700W and 20 mins radiation time. This pyrolysis setup condition has a biochar yield of 57.82 wt%, producing biochar with turbidity reduction of POME as high as 75.01%. Besides, the biochar produced from the optimum pyrolysis setup condition has a SBET of 70.2238 m2/g. The micropore area and micropore volume of biochar is 16.8293 m2/g and 0.008874 cm3/g. The biochar has porous surface, which indicates to the high external surface area of the biochar, making it to have good adsorption capability. Unlike the dried POME sludge, it has no porous surface to be as adsorption site for the adsorption of organic contaminants and colour contaminants. This study showed that the dried POME sludge is a potential waste to be converted into biochar by microwave pyrolysis for adsorption purposes.